The Abundance of Fish Species in Branched (branching) and Table (tabulate) Coral Habitat on Tanjung Beach, Muna Island, Southeast Sulawesi - Muhamad Tasylan; Muhammad Sirih (Universitas Gadjah Mada, 2021)
This research aimed to study the types and abundance of fish which was found in branched and table coral habitat. The quadrate transect method was used at the location of the habitat of branched and table corals. The observation was carried out for 3 days. It was conducted 3 times/day, in the morning, the afternoon, and the evening with ± 10 minutes of observation time for each observation. The method used was transect quadrat 5 m x 5 m with direct observation techniques by means of snorkeling. The types and numbers of individual fish were recorded using the visual census method. Snorkeling was done straightforwardly and looking around by following the contour of the reef. In branching coral habitat, 11 species of fish were found with a total of 66 individuals. On the other hand, on the tabulate reef habitat, there were 9 species of fish with a total of 50 individuals. Both habitats have different types of fish. In the branched coral habitats there were more individual than in the table reef habitats. Fish species found in branched coral habitat and table type fish habitat were different. In branched coral habitats were found more reef fish species than in table coral habitats. These results illustrated that the condition of the coral reefs at Tanjung Beach is still in good condition.